Variation in Serum Total Testosterone Levels in Men with Type 2 Diabetes Mellitus - Jyoti Trivedi; Sangeeta Kapoor; Rahul Arora (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Testosterone is a steroidal hormone that plays an important role in the regulation of carbohydrate, protein, lipid metabolism, thereby control insulin sensitivity. An inverse relationship between serum testosterone, insulin resistance and hyperglycaemia has been well documented. Decreased serum testosterone in Type-2-Diabetes Mellitus (T2DM) promotes accumulation of visceral fat, which increases insulin resistance and in turn, leads to progression of Diabetes Mellitus (DM). Aim: To determine variation in serum total testosterone levels in men with T2DM. Materials and Methods: In the present case-control study, 30 T2DM men (aged 35-55 years) were selected from the OPD of Teerthanker Mahaveer College and Research Centre, Moradabad and 30 healthy age matched individuals, were recruited as controls. Fasting Plasma Glucose (FPG) was estimated by Glucose Oxidase Peroxidase (GOD-POD), end point method. HbA1c was measured by particle enhanced immunoturbidimetric test method and serum testosterone by Enzyme Linked Fluorescent Assay (ELFA) using fully automated VIDAS analyser. Various parameters were analysed using Student’s t-test (independent and unpaired) and the coefficient of correlation was calculated using Pearson’s correlation coefficient. p-value <0.05 were considered as statistically significant, and p-value <0.001 as highly significant. Results: In T2DM patients, serum total testosterone was found to be negatively correlated with FPG (r value=-0.496, p=0.005) and HbA1c (r=-0.548, p=0.002). Out of 30 diabetic patients, 13 (43%) patients had lower level of serum total testosterone when compared to the reference range (<3 ng/mL). The serum total testosterone levels were found to be elevated in diabetic patients with FPG≤200 mg/dL or HbA1c≤6.5 in comparison to patients with FPG>200 or HbA1c>6.5 mg/dL, however the differences were not statistically significant. Relatively comparable serum total testosterone levels were found in diabetic patients with duration of DM≤2 years and DM>2 years, thus suggesting that serum total testosterone concentration might be independent of the duration of DM. Conclusion: Testosterone not only plays a prime role in men’s sexual health but also have an influence on glycaemic status of diabetic patients. Assessment of lower serum total testosterone levels can serve as a useful tool for evaluation of prognosis of T2DM. Therefore, all T2DM patients should be screened for androgen levels and testosterone replacement therapy should be considered to improve overall health of diabetic men.